2020
DOI: 10.1016/j.bbagen.2020.129523
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of striated muscles to Wolframin deficiency in mice: Alterations in cellular bioenergetics

Abstract: Background: Wolfram syndrome (WS), caused by mutations in WFS1 gene, is a multi-targeting disease affecting multiple organ systems. Wolframin is localized in the membrane of the endoplasmic reticulum (ER), influencing Ca 2+ metabolism and ER interaction with mitochondria, but the exact role of the protein remains unclear. In this study we aimed to characterize alterations in energy metabolism in the cardiac and in the oxidative and glycolytic skeletal muscles in Wfs1-deficiency. Methods: Alterations in the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Expression of Wfs1 in the mouse is also seen in a multitude of different tissues, including skeletal and cardiac muscle ( 29 , 30 ) (see also http://www.informatics.jax.org/gxd/marker/MGI:1328355 ). Wfs1 -deficient mice show alterations in protein expression ( 31 ) and energy metabolism ( 32 ) in both muscle tissue types. In vitro assays have also demonstrated that the mammalian Wfs1 protein functions in the nuclear envelope to reposition muscle-specific genes during myogenesis ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Wfs1 in the mouse is also seen in a multitude of different tissues, including skeletal and cardiac muscle ( 29 , 30 ) (see also http://www.informatics.jax.org/gxd/marker/MGI:1328355 ). Wfs1 -deficient mice show alterations in protein expression ( 31 ) and energy metabolism ( 32 ) in both muscle tissue types. In vitro assays have also demonstrated that the mammalian Wfs1 protein functions in the nuclear envelope to reposition muscle-specific genes during myogenesis ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study we investigated alterations in mitochondrial metabolism of Wfs1KO mice muscles and found decreased and less coupled NADH-linked ADP-stimulated respiration in comparison with wild type (WT) littermates [ 43 ]. These alterations were largely substrate-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In Wfs1KO mice muscles the maximal mitochondrial respiration in the presence of Glutamate (Glut) and Malate (Mal) as respiratory system complex I (CI)-linked substrates was decreased in all studied muscle types, accompanied with significantly increased Leak respiration in glycolytic muscles. With Mal and Pyruvate (Pyr) as substrates the increased Leak was detected only in glycolytic muscles (rectus femoris (RF)) and white gastrocnemius (GW)) and decrease in CI linked oxygen consumption was significant only in GW [ 43 , 44 ]. Decrease in adenylate and creatine kinase enzymatic activities of skeletal muscles of wolframin-deficient glucose-intolerant animals and changes in coupling of these enzymes to oxidative phosphorylation (OxPhos) suggest the reconfiguration of energy transport networks and thus could affect muscle performance at higher workloads [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation